1997
DOI: 10.1159/000113398
|View full text |Cite
|
Sign up to set email alerts
|

Freezing Gait in Parkinson's Disease

Abstract: Freezing is a well-known problem in Parkinson''s disease (PD) and is characterized by an abrupt difficulty in starting or continuing rhythmic and repetitive movements. We utilized a questionnaire in order to assess the occurrence of the freezing gait phenomenon (FG) in a population of 100 consecutive PD patients. Our PD population included 70 males and 30 females, with a mean age of 61.1 ± 9.1 years. Mean duration of PD was 6.5 ± 4.0 years. 92/100 patients were under L-Dopa treatment. The FG phenomenon occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 0 publications
7
88
1
Order By: Relevance
“…Our study found that around 47% of patients with PD that attended a Brazilian specialized movement disorder clinic reported FOG. Other previous studies reported variable findings, and this large variability may be probably explained by methodological differences such as the criteria to identify FOG and by the clinical characteristics of the sample evaluated [14][15][16] . Our patients with PD and FOG had a longer disease duration compared to patients without it, which is consonant with previous studies showing a strong association between FOG and the duration and severity of the disease 4,17 .…”
Section: Discussionmentioning
confidence: 83%
“…Our study found that around 47% of patients with PD that attended a Brazilian specialized movement disorder clinic reported FOG. Other previous studies reported variable findings, and this large variability may be probably explained by methodological differences such as the criteria to identify FOG and by the clinical characteristics of the sample evaluated [14][15][16] . Our patients with PD and FOG had a longer disease duration compared to patients without it, which is consonant with previous studies showing a strong association between FOG and the duration and severity of the disease 4,17 .…”
Section: Discussionmentioning
confidence: 83%
“…This is not surprising as it is well known that FOG occurs more frequently as PD progresses. 40,41 It is interesting, though, that the Tango group presented no differences in FOG from baseline to 12 months, suggesting that exercise may delay the progression of FOG. This seems feasible, as tango dancing requires many starts, stops, turns, and movement in confined spaces, thereby incorporating direct practice of walking in the situations that commonly provoke freezing.…”
Section: Physical Functionmentioning
confidence: 95%
“…These falls confer an eight fold greater risk for hip fracture compared to falls during straight walking (Cumming and Klineberg, 1994). Moreover, turning frequently triggers freezing, a sudden interruption of ongoing movement, possibly further increasing fall risk (Giladi et al, 1992, Lamberti et al, 1997, Schaafsma et al, 2003, Bloem et al, 2004. Gordon et al (1995) demonstrated that the somatosensory system involved in directional control of locomotor trajectory through foot contact with the floor, the podokinetic (PK) system, is adaptable in healthy individuals.…”
Section: Introductionmentioning
confidence: 99%